Improving healthcare efficiency through long-term care insurance (LTCI): a super-SBM and DID analysis of 291 Chinese cities - Jin, Tongtong; Halili, Ayitijiang (Frontiers in Public Health, 2025)
BackgroundThe intensification of population aging has exacerbated the strain on medical resources. Long-term care insurance (LTCI) influences healthcare efficiency by redefining the boundaries between medical and care services. However, its mechanisms and effectiveness in developing countries remain underexplored. This study investigates the impact pathways and heterogeneous characteristics of the effects of LTCI on regional healthcare efficiency in China, providing evidence for policy optimization.MethodsUsing panel data from 291 prefecture-level cities in China from 2010–2021, healthcare efficiency was measured via the slack-based measure super efficiency (Super-SBM) model. The difference-in-differences (DID) method was employed to evaluate the policy effects of LTCI. Bootstrap-based mediation models were used to examine the transmission mechanisms of hospitalization volume, average length of stay, and the number of care institutions. Regional heterogeneity was also analyzed.ResultsLTCI significantly improved regional healthcare efficiency (β = 0.071, P < 0.01). Mechanism analysis identified three effective pathways: (1) Reducing hospitalization demand (λ = −0.419, P < 0.01) freed up medical resources, contributing 3.42% of the efficiency gains; (2) Shortening length of hospital stay (λ = −0.326, P < 0.01) accelerated bed turnover, accounting for 47.6% of the total effect, making it the dominant pathway; (3) Expanding institutional care supply (λ = 0.330, P < 0.05) diverted patient flows, explaining 9.23% of the improvement. Heterogeneity analysis indicated that the policy effects were more pronounced in the eastern and central regions and new first- and third-tier cities.ConclusionsLTCI is an effective tool for optimizing the allocation of medical resources. Region-specific strategies should be adopted to increase demand-side incentives and advance supply-side reforms. This study provides new insights for the efficient utilization of medical resources and the design of LTCI systems in developing countries.